The Factors in Formation of the Human Potential of an Innovative Economy - Shevchenko Borys O.; Nepokupna Tetiana A. (Bìznes Inform, 2019)
The article is aimed at defining and theoretically substantiating the factors that influence the formation of the human potential of an innovative economy. The interdisciplinary approach to the analysis of existing scientific developments in this area has identified a lack of depth in scientific analysis of the problem. The article outlines the features of the formation of the human potential of an innovative economy: complexity of the process, duration, unevenness, uncertainty of the final result; it is determined that qualitative characteristics of human potential depend on the intensity and effectiveness of a number of socio-economic, cultural and ideological as well as other processes throughout a person’s life; at least three main groups of the factors influencing the formation of the human potential of an innovative economy are allocated: psychophysiological, professional-qualification and spiritual-moral components; the contents of these factors are disclosed. Prospects for further research on this problem should be the definition and analysis of the institutional conditions of intensification of the process of human development of the innovative economy at a qualitative level.